Highways to Ageing - Linking life course SEP to multivariate trajectories of health outcomes in older adults - Duim, Etienne; Lima Passos, Valéria (Archives of gerontology and geriatrics, 2020)
•Heterogeneous life course paths of SEP were unveiled in an older Mexican population•Mobility, self-rated health and morbidity co-evolve in tandem over time•Variations in temporal connections of health outcomes were observed•Life course socio-economic forces underlie the heterogeneity of ageing pathways•The time is ripe for a dynamic systems approach to ageing Ageing is a temporal, multi-faceted process subject to interacting factors. In this study, we used life course and multidimensional approaches to elucidate the association between socioeconomic forces across a lifetime and the developmental origins in health and disease of the Mexican elderly. Data stemmed from the Mexican Health and Ageing Study, constituting a sample of older adults (N= 5169, ≥50 years). With retrospective information on early, intermediary and contemporaneous socioeconomic indicators, life course typologies of socioeconomic position were identified using Latent Class Analysis. Based on prospective data of functional mobility, number of chronic conditions and self-rated health, multivariate trajectories of health outcomes were uncovered with Group Based Trajectory Model. Links between the extracted SEP and multivariate health latent constructs were explored with multinomial logistic regression. Life course SEP classes were heterogeneous, yet a large proportion of subjects was characterized by persistent socioeconomic adversity throughout life. The health outcomes’ patterns of co-evolution were diverse too, shedding light on the nature of their developmental links, while revealing variable synchronicity in their temporal decline. A graded association was observed between the life course SEP classes and ageing trajectories. The results primarily backed the cumulative advantage/disadvantage life course framework, while finding some indication for age as a leveller hypothesis. Variability in patterns of dynamic co-action among the health outcomes depicts ageing as a naturally variable process of interconnected changes. Life course evidence for the ways socio-economic forces are differentially linked to distinct developmental profiles of ageing is provided.